2014
DOI: 10.1002/cyto.b.21208
|View full text |Cite
|
Sign up to set email alerts
|

Translating the MDS flow cytometric score into clinical practice

Abstract: Myelodysplastic syndromes (MDS) are classified by the WHO as myeloid neoplasms, and are characterized by cytopenia and dysplasia in one or more myeloid cell lines. Recently, a flow cytometric score (FCM-score) was published capable of discriminating low-grade MDS from non-clonal cytopenias (Della Porta et al., 2012). We tested the applicability of the FCM-score in a patient population from a large peripheral teaching hospital in The Netherlands.The evaluation of the proposed FCM score in low-grade MDS showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The Ogata Score performed with reasonable sensitivity and high specificity, as has been reported by others. 11,[13][14][15] The specificity of the flow cytometry score was similar to that of aspirate morphology and trephine morphology, and the sensitivity of flow cytometry was comparable to trephine morphology.…”
Section: Discussionmentioning
confidence: 73%
“…The Ogata Score performed with reasonable sensitivity and high specificity, as has been reported by others. 11,[13][14][15] The specificity of the flow cytometry score was similar to that of aspirate morphology and trephine morphology, and the sensitivity of flow cytometry was comparable to trephine morphology.…”
Section: Discussionmentioning
confidence: 73%
“…The MDS score, which we applied based on analysis of the screening tube, has been developed by Ogata et al. It has been subsequently validated in a multinational study and in a routine diagnostic practice . Recently, a prognostic significance of this score has also been reported .…”
Section: Discussionmentioning
confidence: 99%
“…This score has been validated in an international study and has been reported to be of prognostic significance in MDS patients . It has been recommended to be used for screening purposes by the International/European Leukemia Net Working Group for Flow Cytometry in MDS and confirmed as useful in clinical practice .…”
mentioning
confidence: 99%
“…In this study, we applied the FCS, a cumulative score of 4 IPSs to our sample population, initially reported by Della Porta et al, and subsequently validated in a single center study . Aalbers et al evaluated the FCS score in children with dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we applied the FCS, a cumulative score of 4 IPSs to our sample population, initially reported by Della Porta et al, and subsequently validated in a single center study. 9,10 Aalbers et al 11 evaluated the FCS score in children with dysplasia. The four IPS and cutoff levels comprise of: (a) CD34 + myeloblast-related cluster size (≥2%), (b) B-cell progenitor-related cluster size (≤5%), (c) granulocyte to lymphocyte SSC ratio (≤6), and (d) lymphocytes to myeloblasts CD45 ratio (≤4 or ≥7.5).…”
mentioning
confidence: 99%